Synthesis and Review: Advancing Agricultural Greenhouse Gas Quantification - Olander, L; Wollenberg, Eva Karoline; Tubiello, F.N.; Herold, Martin (IOP Publishing, 2014)
Reducing emissions of agricultural greenhouse gases (GHGs), such as methane and nitrous oxide, and sequestering carbon in the soil or in living biomass can help reduce the impact of agriculture on climate change while improving productivity and reducing resource use. There is an increasing demand for improved, low cost quantification of GHGs in agriculture, whether for national reporting to the United Nations Framework Convention on Climate Change (UNFCCC), underpinning and stimulating improved practices, establishing crediting mechanisms, or supporting green products. This ERL focus issue highlights GHG quantification to call attention to our existing knowledge and opportunities for further progress. In this article we synthesize the findings of 21 papers on the current state of global capability for agricultural GHG quantification and visions for its improvement. We conclude that strategic investment in quantification can lead to significant global improvement in agricultural GHG estimation in the near term.